Expression, Purification and Initial Characterization of Functional α1-Microglobulin (A1M) in Nicotiana benthamiana - Carlsson, Magnus L. R.; Kristiansson, Amanda; Bergwik, Jesper; Kanagarajan, Selvaraju; Bülow, Leif; Åkerström, Bo; Zhu, Li-Hua (Frontiers in Plant Science, 2020)
α1-Microglobulin (A1M) is a small glycoprotein that belongs to the lipocalin protein family. A major biological role of A1M is to protect cells and tissues against oxidative damage by clearing free heme and reactive oxygen species. Because of this, the protein has attracted great interest as a potential pharmaceutical candidate for treatment of acute kidney injury and preeclampsia. The aim of this study was to explore the possibility of expressing human A1M in plants through transient gene expression, as an alternative or complement to other expression systems. E. coli, insect and mammalian cell culture have previously been used for recombinant A1M (rA1M) or A1M production, but these systems have various drawbacks, including additional complication and expense in refolding for E. coli, while insect produced rA1M is heavily modified with chromophores and mammalian cell culture has been used only in analytical scale. For that purpose, we have used a viral vector (pJL-TRBO) delivered by Agrobacterium for expression of three modified A1M gene variants in the leaves of N. benthamiana. The results showed that these modified rA1M protein variants, A1M-NB1, A1M-NB2 and A1M-NB3, targeted to the cytosol, ER and extracellular space, respectively, were successfully expressed in the leaves, which was confirmed by SDS-PAGE and Western blot analysis. The cytosol accumulated A1M-NB1 was selected for further analysis, as it appeared to have a higher yield than the other variants, and was purified with a yield of ca. 50 mg/kg leaf. The purified protein had the expected structural and functional properties, displaying heme-binding capacity and capacity of protecting red blood cells against stress-induced cell death. The protein also carried bound chromophores, a characteristic feature of A1M and an indicator of a capacity to bind small molecules. The study showed that expression of the functional protein in N. benthamiana may be an attractive alternative for production of rA1M for pharmaceutical purposes and a basis for future research on A1M structure and function.